ROLE OF MOLECULAR OXYGEN IN THE DISSOLUTION OF SIDERITE AND RHODOCHROSITE - Duckworth O.W.; Martin S.T. (My University, 2004)
The dissolution of siderite (FeCO 3) and rhodochrosite (MnCO 3) under oxic and anoxic conditions is investigated at 298 K. The anoxic dissolution rate of siderite is 10 -8.65 mol m -2 s -1 for 5.5 < pH < 12 and increases as [H + ] 0.75 for pH 4 to pits elongated at one vertex for pH < 4. Under oxic conditions the dissolution rate decreases to below the detection limit of 10 -10 mol m -2 s -1 for 6.0 < pH 10.3, the oxic dissolution rate is as high as 10 -7.5 mol m -2 s -1 , which is greater than under the corresponding anoxic conditions. A fast electron transfer reaction between solution O 2 or [Fe 3+ (OH) 4 ] - species and surficial >Fe II hydroxyl groups is hypothesized to explain the dissolution kinetics. AFM micrographs do not show precipitation under these conditions. Anoxic dissolution of rhodochrosite is physically observed as rhombohedral pit expansion for 3.7 < pH < 10.3 and is chemically explained by parallel proton- and water-promoted pathways. The dissolution rate law is 10 -4.93 [H + ] + 10 -8.45 mol m -2 s -1 . For 5.8 < pH 7.7 under oxic conditions, the dissolution rate decreases from 10 -8.45 to 10 -9.0 mol m -2 s -1 . Flattened hillock precipitates grow across the entire surface without apparent morphological influence by the underlying rhodochrosite surface. XPS spectra and thermodynamic calculations implicate the precipitate as bixbyite for 5.8 < pH 7.7.